Alcohol Oxidation in the Presence of Methyl Chlorosulfonate and Dimethyl Sulfoxide. Issue 23 (17th June 2020) - Davidovich, Yuriy A.; Kozlov, Sergei V.; Smushkevich, Yuriy I.
Abstract: The reaction of methyl chlorosulfonate with dimethyl sulfoxide (DMSO) was studied at various temperatures. The interaction of dimethyl sulfoxide‐sulfur trioxide complex with various alcohols in the presence of triethylamine (Et3 N) was investigated. The results showed that this complex oxidizes the primary and secondary alcohols to the corresponding carbonyl compounds in excellent yields. Abstract : For the first time, it has been shown that reaction between methyl chlorosulfonate and dimethyl sulfoxide at –78°C producing dimethyl sulfoxide‐sulfur trioxide complexes of the general structure (DMSO)x SO3, where x varies from 1 to 3. The complexes oxidize primary and secondary alcohols in the presence of triethylamine at r.t. to corresponding carbonyl compounds in excellent yields.